2020
DOI: 10.1111/odi.13420
|View full text |Cite
|
Sign up to set email alerts
|

Oral bacterial diversity is inversely correlated with mucosal inflammation

Abstract: Objective We investigated the relationship amongst the oral mucosal bacterial community, clinical severity and inflammatory markers in the two most common immune‐mediated oral mucosal diseases, namely recurrent aphthous stomatitis (RAS) and oral lichen planus (LP). Methods Patients with RAS (n = 15) and LP (n = 18) and healthy controls (n = 13) were recruited using criteria to reduce the effect of factors that influence the microbiota structure independently of oral mucosal disease. Clinical severity was quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 43 publications
3
10
0
Order By: Relevance
“…The alpha diversity of the oral microbiota was significantly reduced in the stress group compared to the controls. Reduced alpha diversity has been observed in patients with RAS and oral lichen planus [ 46 ]. Our findings may be consistent with the concept that psychological stress is an etiology of RAS and oral lichen planus [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The alpha diversity of the oral microbiota was significantly reduced in the stress group compared to the controls. Reduced alpha diversity has been observed in patients with RAS and oral lichen planus [ 46 ]. Our findings may be consistent with the concept that psychological stress is an etiology of RAS and oral lichen planus [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral inflammation is a common physiological immune response that if persists may produce damage as well as increase the risk of progression to lesions ( 15 ). In addition, the oral mucosa may be accompanied by a low-grade chronic upregulation of inflammatory mediators that may be associated with microbes ( 16 ). A previous study proposed that certain low abundance microbial pathogens can interfere with the host immune system and remodel the microbiota, leading to oral inflammatory diseases such as gingivitis and periodontitis ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oral microbiota such as Prevotella and Ruminococcaceae were positively associated with IL-1β while Prevotella and Granulicatella were negatively associated with IL-8 [86] . In another study, a negative correlation was observed between microbial alpha diversity and salivary interferon-γ, interleukin-17A, and interleukin-1β in patients with stress-related diseases such as oral lichen planus and recurrent aphthous stomatitis [73] . Salivary glands may affect the oral microbiome by acting as a route to transmit microbiota into saliva.…”
Section: Psychological Stress and Oral Microbesmentioning
confidence: 91%
“…Consistent with our findings, a previous experiment on wild red squirrels showed that the alpha diversity of the oral microbiome was lower in those with elevated fecal glucocorticoid metabolites, a measure of the hypothalamic-pituitary-adrenal axis [60] . Clinically, reductions in the alpha diversities of the oral microbiome have been observed in stress-related oral diseases, such as recurrent aphthous stomatitis, oral lichen planus, and Sjogren’s syndrome [73] . These findings indicate that a reduction in the alpha diversity of the oral microbiome might be associated with psychological stress.…”
Section: Psychological Stress and Oral Microbesmentioning
confidence: 99%